HIGH ANION GAP METABOLIC ACIDOSIS IN SEVERE DELIBERATE POISONING WITH METFORMIN – SUCCESSFUL TREATMENT WITH 2.5-HOUR CONVENTIONAL HEMODYALISIS - Petkovska Lidija; Brezovska-Kavrakova J; Petronijevik Z; Smokovski I; Zafirova B (Macedonian Association of Anatomists, 2020)
Metformin-associated lactic acidosis is a rare, life-threatening condition with a high mortality rate, that could occur both with therapeutic use and in metformin overdose. Clinical manifestations may be nonspecific, with severe anion gap metabolic acidosis and elevated lactate levels being the most prominent laboratory findings; hence, delaying the diagnosis and treatment. Renal replacement therapy plays a key role in the treatment of severe metformin poisoning. We herewith present a case with intentional metformin poisoning successfully treated with one session of hemodialysis in combination with parenteral sodium bicarbonate therapy. A 17-year-old non-diabetic woman ingested 25 grams of metformin in a suicide attempt. She developed vomiting and diarrhoea and was brought to the local emergency unit, and shortly after admittance she became nonresponsive. Glasgow coma scale was 7/15 (E2, V1, M4), glucose level was 3.4 mmol/L and blood pressure was 90/60 mmHg. The first arterial blood gas analysis demonstrated a severe metabolic acidosis with high lactate level (pH = 6.778, BE -31.7, lactate 18 mmol/L, anion gap 39.8 mmol/L), and, subsequently, she developed a non-oliguric renal failure. Lactic acidosis was successfully treated with a combination of a conventional 2.5-hour bicarbonate HD and early administration of intravenous bicarbonate. The arterial pH steadily increased back to normal levels, lactic acidosis improved and kidney function recovered completely. It could be concluded that even a single session of timely applied conventional HD in combination with parenteral administration of bicarbonates allows simultaneous drug removal, lactate reduction and acid-base correction and should be a treatment of choice in hemodynamically stable patients with severe metformin poisoning.
Keywords: metformin poisoning; lactic acidosis; renal replacement therapy